Análisis biomecánico del lanzamiento con estólica - Coros Villca, Carlos (2021)
In recent years, evidence-based medicine has generated the need to quantify any movement, objectively. Today, thanks to the development of electronics and computing, new techniques have been developed, such as approaching biomechanical studies. One of them is 3D photogrammetry. In this way, the present work aims to evaluate the technical launch gesture with atlatl, through a biomechanical analysis using the 3D Photogrammetry tool and the bioinformatics application: Ariel Performance Analysis System (APAS 2000 3D), in order to infer in this way Musculoskeletal Stress Markers involved in it. The results show that the sites subjected to the greatest stresses are those related to shoulder acceleration, and therefore this joint is the most compromised, which is consistent with similar findings in certain related sports and the pathology associated with throwing. Therefore, we disagree with the term «Elbow of Atlatl» that is still used by many anthropologists. It is suggested to be more cautious when interpreting the activity patterns related to this technical gesture.